1970
DOI: 10.1179/pom.1970.13.25.002
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Parameters Influencing Some Mechanical Properties of Tungsten Carbide–cobalt Alloys

Abstract: The paper reviews experimental results relating to the influence of composition, structure, and testing conditions on the hardness, compressive strength, and transverse rupture strength of sintered tungsten carbide-cobalt alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(73 citation statements)
references
References 19 publications
2
71
0
Order By: Relevance
“…Crack propagation induces a local stress release. This aspect is in a good agreement with the fineness of the fragments reported in [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Hard Metals: Overview and Some Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…Crack propagation induces a local stress release. This aspect is in a good agreement with the fineness of the fragments reported in [53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Hard Metals: Overview and Some Propertiessupporting
confidence: 92%
“…[6,55,56], WC-Co hard metals, developed from an ultrafine or nanograined particles, show superior hardness compared to their coarser-grained based ones, while Lankford [57] indicates that the compressive strength of these hard metals increases when binder contents decreases. The influence of the loading rate on the compressive strength of WC-Co hard metal is illustrated in [52] as a function of Co content and the authors found that the fragments results to be finer after compressive loading with increasing strain rate and as Co content decreases, the compressive strength increases due to the increasing level of failure which is characterized by crack initiations, typical features for brittle material.…”
Section: Hard Metals: Overview and Some Propertiesmentioning
confidence: 99%
“…[18][19][20] As mentioned in chapter 3.2, TRS has a substantial increase after the addition of 2.5 mass% seeds. The increase of WC grain size brings about the increase of TRS to a certain degree.…”
Section: 2mentioning
confidence: 99%
“…1)3) Functionally graded material (FGM) WCCo is a class of these composites combines two or more irreconcilable properties in the same component, for instance, hardness and fracture toughness. 4)6) Generally, hardness and wear resistance are often improved at the expense of the fracture toughness, Meanwhile, the multi-layered structure is a possible solution used to improve them all in the same component.…”
Section: Introductionmentioning
confidence: 99%